2019
DOI: 10.5005/jp-journals-10071-23248
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion Thresholds in Critically Ill Patients

Abstract: Anemia of multifactorial etiology is common among critically ill patients and several arbitrary transfusion thresholds have been proposed. Transfusion of red blood cells has been well established to increase morbidity and even mortality among critically ill patients. Several randomized controlled studies have evaluated the use of a restrictive compared to a more liberal transfusion strategy in the critically ill. A transfusion threshold of 7 g/dL appears to be generally safe, especially in the younger age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, blood transfusion is expensive and not an innocuous treatment. Transfusions are associated with pulmonary complications, sepsis, thromboembolic events, and mortality [ 24 , 25 , 26 , 27 ]. However, RBC transfusion may be harmful even in the geriatric age group, where anemia is tolerated less, in patients with cardiovascular disease, cancer, or in patients receiving beta-blocker therapy [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, blood transfusion is expensive and not an innocuous treatment. Transfusions are associated with pulmonary complications, sepsis, thromboembolic events, and mortality [ 24 , 25 , 26 , 27 ]. However, RBC transfusion may be harmful even in the geriatric age group, where anemia is tolerated less, in patients with cardiovascular disease, cancer, or in patients receiving beta-blocker therapy [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, existing studies have reported that some subsets of patients may benefit from RBCs to maintain higher hemoglobin concentrations and that future research should focus on these clinical contexts [ 31 ]. A recent study stated that a threshold value of 7 g/dL for RBC transfusion in critically ill patients in the intensive care unit is generally reliable [ 26 ]. The authors believe that a cut-off Hb value, determined as a general recommendation, can be decisive in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that transfusion of red blood cells may increase the mortality rate of critically ill patients. 28,29 Anemia associated with sepsis is not always true anemia, and sometimes it may be caused by blood dilution related to fluid load. 30,31 Therefore, after occurrence of sepsis, even if the HC is reduced, clinicians need to determine whether a blood transfusion is required on the basis of the condition of children.…”
Section: Discussionmentioning
confidence: 99%